Analisis Penerapan Sistem Akuntansi Keuangan Pemerintah pada Kantor Kecamatan Sukaraja Kabupaten Sukabumi: (Studi Kasus pada Kantor Kecamatan Sukaraja) - Marlina Banjarnahor; Darmo H. Suwiryo; Evi Martaseli (AKUNTANSI 45, 2024)
Increasing the well-being and welfare of the Indonesian people and state cannot be separated from the management of the regional economy. Decision makers in regional public authorities need to pay attention to regional financial management, implement good accountability and openness in this field by implementing a financial accounting system. This research aims to determine and explain the analysis of the implementation of the government financial accounting system at the Sukarja Sukabumi District office. This research was conducted using qualitative descriptive research. The selection of informants in this research uses the method of selecting informants or sources who have certain objectives in accordance with the research subject. The data sources used are primary and secondary sources. Data collection was carried out through field research through observation, interviews and documentation. The results of this research show that even though the implementation is still not optimal, the implementation of accounting at the Sukaraja sub-district government Finance and Assets Agency, Sukabumi Regency is in accordance with the established guidelines.The application of accounting has been in accordance with Government Regulation No. 71 of 2010 as well as the completeness of the financial statement items has been in accordance with the provisions of the SKPD financial statements consisting of Budget Realization Reports, Balance Sheets, and Notes on Financial Statements. The recording and classification of transactions comes from bookkeeping evidence, which is then recorded in a journal book.